Faculty feedback that begins with resident self‐assessment: motivation is the key to success. Issue 3 (4th December 2017) - Moroz, Alex; Horlick, Margaret; Mandalaywala, Neil; T Stern, David
Abstract : Context: The seeking and incorporating of feedback are necessary for continuous performance improvement in medicine. We know that beginning feedback conversations with resident self‐assessment may reduce some of the tensions experienced by faculty staff. However, we do not fully understand how residents experience feedback that begins with self‐assessment, and whether any existing theoretical frameworks can explain their experiences. Methods: We conducted a constructivist grounded theory study exploring physical medicine and rehabilitation residents' experiences as they engaged in a structured self‐assessment and faculty staff feedback programme. Utilising purposive sampling, we conducted 15 individual interviews and analysed verbatim transcripts iteratively. We implemented several procedures to enhance the credibility of the findings and the protection of participants during recruitment, data collection and data analysis. After defining the themes, we reviewed a variety of existing frameworks to determine if any fitted the data. Results: Residents valued self‐assessment followed by feedback (SAFF) and had clear ideas of what makes the process useful. Time pressures and poor feedback quality could lead to a process of 'just going through the motions'. Motivation coloured residents' experiences, with more internalised motivation related to a more positive experience. There were no gender‐ or year of training‐related patterns. Conclusions: Self‐determination theory provided the clearest lens for framing our findings and fitted into a conceptual model linking the quality of the SAFF experience and residents' motivational loci. We identified several study limitations including time in the field, evolving characteristics of the SAFF programme and the absence of faculty voices. We believe that by better understanding residents' experiences of SAFF, educators may be able to tailor the feedback process, enhance clinical performance and ultimately improve patient care. Abstract : Moroz et al. demonstrate that residents value some aspects of self‐assessment followed by feedback, while identifying barriers and facilitators influencing the success of such interactions.